Rebranding rule : images of restoration and revolution monarchy, 1660-1714 - Sharpe, Kevin (Kevin M.) (Yale University Press, 2013)
"In the climactic part of his three-book series exploring the importance of public image in the Tudor and Stuart monarchies, Kevin Sharpe employs a remarkable interdisciplinary approach that draws on literary studies and art history as well as political, cultural, and social history to show how this preoccupation with public representation met the challenge of dealing with the aftermath of Cromwell's interregnum and Charles II's restoration, and how the irrevocably changed cultural landscape was navigated by the sometimes astute yet equally fallible Stuart monarchs and their successors."--